2022
DOI: 10.3390/cancers14122995
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Skin–Gut Axis to Immune-Related Adverse Events with Multi-System Involvement

Abstract: Immune-related adverse events (irAEs) frequently complicate treatment with immune checkpoint blockade (ICB) targeting CTLA-4, PD-1, and PD-L1, which are commonly used to treat solid and hematologic malignancies. The skin and gastrointestinal (GI) tract are most frequently affected by irAEs. While extensive efforts to further characterize organ-specific adverse events have contributed to the understanding and management of individual toxicities, investigations into the relationship between multi-organ toxicitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…For example, phototherapy with UVBnb or specific biologics (e.g., TNF-blockade or apremilast) will be preferred for psoriasiform skin AE. In the case of Grade 2 or higher pruritus, GABA analogues, such as pregabaline or gabapentine can be introduced starting at low initial doses [ 31 ]. In acneiform rashes, topical antibiotics such as clindamycin or oral tetracyclines will be prioritized over topical corticosteroids [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, phototherapy with UVBnb or specific biologics (e.g., TNF-blockade or apremilast) will be preferred for psoriasiform skin AE. In the case of Grade 2 or higher pruritus, GABA analogues, such as pregabaline or gabapentine can be introduced starting at low initial doses [ 31 ]. In acneiform rashes, topical antibiotics such as clindamycin or oral tetracyclines will be prioritized over topical corticosteroids [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is based on the grade of ICI-BP. The treatment approach recommended is to continue ICI treatment in grade 1 DAEs and provide BP-specific medications; however, if grade 2 or higher, anti-cancer therapy should be held until the DAE resolves to grade 0 or 1 [81,82]. Medications include topical corticosteroids, oral corticosteroids, and sys-temic steroid-sparing drugs such as methotrexate, dapsone, azathioprine, mycophenolate mofetil, omalizumab, dupilumab, rituximab, or IVIg [4,[83][84][85][86].…”
Section: Bullous Pemphigoid (Bp)mentioning
confidence: 99%
“…The importance of these teams becomes even more evident when exploring the relationships between ciRAEs, irAEs in other organs, and patterns of malignancy response and resistance.Novel single-cell RNA sequencing and multi-spectral flow cytometry have recently been reported in relation to ICI-induced colitis. The correlation between the skin-gut axis with immune-related adverse events has been well described,44 and the study of the molecular mechanisms of irAEs affecting the gastrointestinal tract can have important implications relating to cirAEs. Using TCRαβ analysis, Luoma et al demonstrated a connectivity between CD8+ tissueresident memory T cells in the gastrointestinal tract and emergence of cytotoxic effector cells in patients with checkpoint inhibitorinduced colitis.…”
mentioning
confidence: 99%